The Impact of virtual groups in social media programs on changing the social habits of university students – An applied study on female students of Qassim University – - Al Harbi, Ahlam Hamid Mohammed; Al-Saif, Mohammed Ibrahim (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the impact of virtual groups in social networking programs on changing social and economic customs among female university students. To achieve this, the study relied on the social survey method. The closed questionnaire tool was used to collect data. The study was applied to female students of Qassim University from Faculty of pharmacy, Faculty of sharia (Islamic Law) and Faculty of Arts, the number of the sample was (273) students, and were chosen in a stratified manner. In the light of the hypothesis of the explained theories, which are (social progress, proliferation, determination, cultural courses), the study reached a number results, the most important of which are: that Arabic and foreign social materials shared among female members of virtual groups, whether among relatives or friends or among work groups, are related to the change of social customs of young woman’s engagement in Saudi society, so that it is directly from the suitor to the young woman without an intermediary before asking the guardian. The study also found that there is a relationship between the virtual group of female friends and the virtual group of relatives in social networking programs and the change in the expenditure and consumption habits of female university students. The study also reached that there is no relationship between virtual groups and the type of material shared and the level of contentment of the article sent with the customs of the first months of marriage (honeymoon). The customs of honeymoon have changed because of the cultural contact with foreign societies. It turns out that the interpretation of the economic imperative and the interpretation of cultural courses and the interpretation of proliferation are all suitable to interpret the connection of virtual groups in social networking programs with the change of social customs.The study concluded with a number of recommendations, most notably: The need to raise the awareness of parents and family regarding the enlightenment of young women who are getting married about the importance of taking into consideration the rationalization when setting up wedding ceremonies in Saudi society, and that arranging them should be in a modern style with taking into account the values and customs of Saudi society. The study came to a conclusion as a whole that there is an impact of the new social networking on the change of social and economic customs of young women in university. This enhances the importance of conducting and testing a number of different theories. This work would be done through working on more studies and researches which seek the relation between one of social networking programs and consumption. Also, the relation of social networking programs with the change of the concepts, roles and responsibilities of marriage and marital relationship. This would be done through using qualitative and quantitative tools (focused interview, content analysis, case study) in order to describe and interpret aspects that cannot be discovered by the questionnaire.
Keywords: virtual groups; social habits; marriage; consumer behavior